The Construction Site Management for Reconstruct Work: Case Study in Melaka - Asyraf, Muhammad Asyraf Bin Rosman (Progress in Engineering Application and Technology, 2021)
Construction management at the site is a key factor in the effective implementation of large-scale projects. Precise and timely knowledge of on-site job activities and building resources promotes decision-making to enhance efficiency of project management. However, because of rough construction conditions, it is difficult for engineers to gather and exchange information in real time. Thus, this research study is based on identifying the causes and finding out suitable methods that need to be applied by conducting survey for the contractor involved in Sekolah Tunas Bakti Sungai Lereh, Klebang and the company that were selected for this project are Raza Gemilang Enterprise. Furthermore, there is no special method such as computer programing to obtain the data results. With that, the information obtained to complete this research study are from references and cooperation materials as well as interviews and mainly using surveys in the questionnaire. The result shows that, the company should have more workers and quality control of the material is important to avoid the complaint from the client.